The Relationship Between Social Skills, Psychological Well-Being, and Academic Performance in University Students in Chimbote, Peru - Arhuis-Inca, Wendy (2023)
Objective. To identify how social skills, psychological well-being, and academic performance are related in a private university in Chimbote, Peru. Methodology. A correlational-transversal study was conducted on 313 students from the Professional School of Education. The study implemented inventory instruments of social situations (ISS) and Ryff’s psychological well-being scales. In addition, students’ average note for the 2018-II semester was obtained. Results. The results reported that the higher the social skills and the greater the psychological well-being, the higher the academic performance (R = 0.60 and 0.71, p <0.05). Likewise, the higher the social skills, the greater the psychological well-being (R = 0.52, p <0.05). As well, the level of social skills and psychological well-being presented a low level (33.54% and 34.18%, respectively), while academic performance was at a medium level (42.49%). Conclusion. University students presented a deficit at the levels of study variables; at the same time, a positive relationship does exist between them.